2016
DOI: 10.1021/acs.joc.6b02020
|View full text |Cite
|
Sign up to set email alerts
|

Rh(III)-Catalyzed C–H Functionalization of Indolines with Readily Accessible Amidating Reagent: Synthesis and Anticancer Evaluation

Abstract: The rhodium­(III)-catalyzed direct C–H functionalization of various indolines with 1,4,2-dioxazol-5-ones as new amidating agents is described. This transformation provides efficient preparation of C7-amidated indolines known to display potent anticancer activity. The synthetic compounds were evaluated for in vitro anticancer activity against human prostate adenocarcinoma cells (LNCaP), human endometrial adenocarcinoma cells (Ishikawa), and human ovarian carcinoma cells (SKOV3). Compound 4f was found to be high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Carboxylic acidw as found to serve as an effective directing group in the current CÀHa midation with dioxazolone. Indeed, benzoica cids, 2-thiophenecarboxylic acid, and methacrylic acid were all amidated in satisfactory yields (10)(11)(12). Again, the amidation efficiency in reactions of these carboxylic acids with azide was seen to be much poorer.I na ddition, amidationo f N,N-dimethylphenyl carbamate occurred smoothly (13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carboxylic acidw as found to serve as an effective directing group in the current CÀHa midation with dioxazolone. Indeed, benzoica cids, 2-thiophenecarboxylic acid, and methacrylic acid were all amidated in satisfactory yields (10)(11)(12). Again, the amidation efficiency in reactions of these carboxylic acids with azide was seen to be much poorer.I na ddition, amidationo f N,N-dimethylphenyl carbamate occurred smoothly (13).…”
Section: Resultsmentioning
confidence: 99%
“…[8a] We demonstrated that ar hodacyclicc omplex was successfully coupled with sulfonyl azides, affording CÀNc oupled Rh-amido complex at elevated temperature. [8d] This notable outcome inspired extensive subsequents tudies with dioxazolones as the amide source, especiallyf ocusing on the development of Rh III , [10] Ru II , [11] or Co III[12] catalysts, leading to broad applicationsi nt he facile preparation of synthetic valuables. Detailed mechanistic studies strongly corroborated the involvemento fo rganometallic Rh V and Ir V -imido species as the key intermediates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituted dioxazolones were instead employed for the carboxyamidation of indolines at the C7 position at room temperature (or 80 °C for several examples, Scheme 144B ). 853 The reaction proceeds giving generally good yields. Interestingly, the reaction proved efficient on tetrahydroquinoline as well, a not commonly studied substrate.…”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 95%
“…In contrast, the formation of acyl amide with indoline using C–H functionalization is limited, which may be due to the competitive Curtius rearrangement with acyl azides that can lead to C–C bond formation . Recently, Kim and co‐workers reported a Rh‐catalysed coupling of dioxazolones with indolines to give acyl amides,[10a] while Prabhu group accomplished the transformation utilizing Ru‐catalysis (Scheme a). [10b] Li group showed a few examples for the acetyl chelated direct coupling of acyl azide with indoline under Ir‐catalysis devoid of Curtius rearrangement (Scheme b).…”
Section: Introductionmentioning
confidence: 99%